A Systematic Review of Optimal Power Flow Studies with Renewable Energy Sources Penetration - Maulana, Ricky; Syafii, Syafii (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
The increasing penetration Renewable Energy Source (RES) in electrical power grid, the power system must minimize costs and comply with operational and safety requirements. Optimal power flow (OPF) contributes to this objective by determining the optimal control settings, satisfying system and safety constraints, and enhancing operational efficiency. A systematic review was conducted to assess how OPF studies have been evaluated in the literature. The review analyzed 64 journal articles to identify specific OPF studies from three perspectives: type of RES penetration, objective function, and method of OPF. The results indicate that (a) wind turbines are the most commonly used RES model in OPF studies, (b) cost function is the primary objective that the majority of research has considered, and (c) novel meta-heuristics have often been used in OPF methods under uncertain RES penetration. This systematic review identifies research gaps and topics for further research to study OPF with RES penetration. The findings are expected to benefit researchers in deciding the best OPF method under uncertain RES.